Metodologias fotocatalíticas para funcionalização do carbonato de Morita-Baylis-Hillman - Marchini, Lucas (Universidade Federal de São Carlos, 2024)
Morita-Baylis-Hillman (MBH) adducts are well-established building blocks in organic synthesis, renowned for their reaction versatility. The ease with which their structures can be modified makes them ideal for the construction of complex molecules, such as those of pharmacological interest. When converted into carbonates, MBH adducts become highly susceptible to allylation reactions, often employing nucleophilic substitution methodologies. Photoredox catalysis, a highly relevant synthetic tool, enables organic transformations via radicals under mild conditions, facilitating the functionalization of the alkene portion connected to electron-withdrawing groups, which act as excellent radical acceptors. We explored this reactivity in two studies. In the first, we employed an organophotocatalytic protocol using 1,2,3,5-tetrakis(carbazol-9-yl)-4,6-dicyanobenzene (4CzIPN) to generate carbamoyl radicals from 4-carbamoyl-dihydropyridines (carbamoyl-DHPs), yielding 29 examples of polyfunctionalized molecules with up to 98% yields. The robustness of the protocol was demonstrated through monitoring experiments and scale-up. In the second study, we replaced the homogeneous photocatalyst with mesoporous graphitic carbon nitride (mpg-CN), a heterogeneous photocatalyst. This new system was effective not only for carbamoylations but also for methylations, acylations, and non-classical glycosylations from 1,4-dihydropyridines (1,4-DHPs), exhibiting broad functional group tolerance across 50 examples of substrates, with yields reaching up to 80%. The reuse of the photocatalyst was also explored, showing excellent results and confirming the robustness of the adopted strategy.
Photocatalytic methodologies for functionalization of Morita-Baylis-Hillman carbonate
Keywords: Morita-Baylis-Hillman; Alilação; Catálise fotoredox; Radicais; Fotocalisador homogêneo; 4CzIPN; 1,4-diidropiridina; Fotocalisador heterogêneo; Nitreto de carbono; CIENCIAS EXATAS E DA TERRA::QUIMICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::FISICO-QUIMICA ORGANICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::FOTOQUIMICA ORGANICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::SINTESE ORGANICA; 9. Indústria, Inovação e Infraestrutura